Exposure to salinity stress cause ovarian disruption in a stenohaline freshwater teleost, Heteropneustes fossilis (Bloch, 1794). (6th February 2020) - Mohanty, Banalata; Gupta, Kunal; Babu, Gyan; Pal, Himanshu; Verma, Pradeep
Abstract: Stenohaline freshwater fish with narrow salinity tolerance are susceptible to saline stress from global climate change and anthropogenic activities. The present study elucidated that saline exposure during the sensitive window of preparatory phase of oocyte maturation significantly affected gonadosomatic index, ovarian histology and morphometric features of oocytes in a stenohaline freshwater catfish, Heteropneustes fossilis (Bloch, 1794) in a dose (2 ppt, 5 ppt)—and duration (8, 24 days)‐dependent manner. The gonads of H. fossilis show annual maturation cycle. Loss of integrity of ovigerous lamellae, disruption of ovarian stroma, disrupted oolemma, ooplasmic vacuolization, damaged germinal vesicles and altered morphometry of previtellogenic oocytes, such as chromatin‐nucleolus, early perinucleolar and late perinucleolar, elucidated consistent effects of saline exposure except at 8 days exposure to 2 ppt of saline. Increased salinity might have affected the transmembrane ion/water transport and disrupted the osmotic balance in ovary that eventually led to impairment in growth of ovary and oocyte maturation. The susceptibility of ovary to comparatively less concentrations of saline exposure might be due to sensitiveness of ovary/oocytes during the early phase of growth. Fluctuating salinity along with other stressors can affect metabolic and growth rates, fecundity and ultimately survival of fish.